Report of the expert consultation on the development of international guidelines for the ecolabelling of fish and fishery products from inland capture fisheries, Rome, 23 - 26 May 2006
The Expert Consultation took as its main working document the Guidelines for the Ecolabelling of Fish and Fisher Products from Marine Capture Fisheries adopted by the twenty-sixth session of the Committee on Fisheries and published by FAO in 2005. The Consultation made various additional and amendments to this document for it to be suitable fro inland capture fisheries. Many of these amendments derived from including culture-based and enhanced fisheries into the definition of inland capture fisheries. Amendments concerned mostly the sections addressing management systems, stocks under consideration, ecosystem considerations and methodological aspects. Aquaculture was excluded from the scope of the guidelines.